Cutting Costs to Live Within Your Income - Josephine Turner; Michael Gutter; Nayda I. Torres (EDIS)
Revised! FCS-7009, a 3-page fact sheet by Josephine Turner, Michael Gutter, and Nayda I. Torres, advises families in making a spending plan and provides tips for reducing spending. Published by the UF Department of Family Youth and Community Sciences, February 2009.